2018
DOI: 10.1108/cr-04-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Management design as a strategic lever to add value to corporate reputation competitiveness in higher education institutions

Abstract: Purpose The purpose of this paper is to aid the convergence of design and management as a strategic lever and innovative tool to improve corporate reputation in higher education institutions (HEIs), particularly in the Polytechnic Institute of Bragança, Portugal (IPB). Design/methodology/approach SWOT analysis is used to identify strengths and weaknesses in the context of an organization’s internal competencies (identity) and opportunities and threats in an analysis of the organization’s external competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
0
25
0
3
Order By: Relevance
“…More predictors identified in the literature include research performance, quality of student, program value, placement success, the order of entry and media rankings (Saf on, 2009). Identity and image of HEIs (Maduro et al, 2018), research, teaching and internationalization (Delgado-M arquez et al, 2012 are relevant drivers of HEIs reputation on the global context.…”
Section: Antecedents Of Corporate Reputation In Heismentioning
confidence: 99%
See 1 more Smart Citation
“…More predictors identified in the literature include research performance, quality of student, program value, placement success, the order of entry and media rankings (Saf on, 2009). Identity and image of HEIs (Maduro et al, 2018), research, teaching and internationalization (Delgado-M arquez et al, 2012 are relevant drivers of HEIs reputation on the global context.…”
Section: Antecedents Of Corporate Reputation In Heismentioning
confidence: 99%
“…However, both antecedents and consequences of corporate reputation are complicated and specific to a setting and stakeholder (Ali et al, 2015;Ruiz et al, 2016), such as customers in a service organization (Walsh et al, 2009) and employees and students in HEIs. Few studies have investigated antecedents of reputation in HEIs related to employees (Seman and Zulhamri, 2012;Maduro et al, 2018). This paper intends to build from the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…These resources can be the company's employees, the technologies, the business knowledge, the processes or procedures, the equipment or machinery, the brand value or even the financial capital (Wernerfelt, 1984). Previous studies in the higher education industry suggested that the resources, such as internal structures, organizational culture, management designs and leadership styles, influence the success or failure of the higher education institutions and the mergers in this sector (Chipunza and Gwarinda, 2010; Kitchener, 2002; Maduro et al , 2018; Manona, 2015; Ngcamu, 2017). On the other hand, the rivalry levels and the intensified competition were the major forces behind the increasing rate of mergers, and many higher education institutions opt for participating in mergers as a way to establish a competitive advantage in the industry (Boling et al , 2017; Hammond, 2016; Johnes, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, to increase their efficiency and effectiveness, universities behave strategically, trying to make the most of their resources by focussing on those activities in which they advance their competitors (Antonelli, 2008). According to de la , as different activities address the needs of specific stakeholders, universities display heterogeneous activity profiles and stakeholder orientations very much influenced by their resources and structural CR 31,3 characteristics (path dependency) but also by their territory (especially their economic characteristicssee Stonkiene et al, 2016), strategic planning and intangible assets (such as the university reputationsee Maduro et al, 2018). This entails that socio-economic benefits arising from university-industry interactions significantly differ within countries and from one university to another.…”
Section: Introductionmentioning
confidence: 99%